"You Spun Gold Out of This Hard Life": Feminist Worldmaking Practices in the Transmedia Storyworld of Beyoncé's Lemonade - Hutten, Rebekah (Université d'Ottawa / University of Ottawa, 2018)
This thesis examines the ways in which Beyoncé Knowles-Carter’s 2016 album Lemonade works as a culturally significant text in the realm of popular media. Situated within Black feminist theoretical concepts of freedom practices and Black Feminist Love Politics, the thesis argues that Lemonade mobilizes stylistic and strategic intertextual references to develop a transmedia storyworld within a paradigm of resistance to, and healing from, white supremacist histories. Such intertextual information exists within the musical, lyrical, visual, poetic, and transmedia domains of Lemonade. The transmedia extensions include interviews, live performances, speeches, social media posts, and photoshoots. Combined with theories from Black feminist thought of freedom practices—which include talking back (bell hooks 1989), dark sousveillance (Simone Browne 2015), and interruptions to whiteness (DiAngelo 2011)— and Black Feminist Love Politics (Jennifer Nash 2013), the intertextual data present in Lemonade can be analyzed using methodologies from the field of popular musicology (intertextuality and mediality).
Keywords: Feminist theory; Critical race studies; Musicology; Popular music; Digital media; Transmedia; Worldmaking; Music video; Beyonce; Visual album